Diseases, grievances, and public health notification events: Result of treatment among indigenous children (Research, Society and Development, 2021)
Introduction: Compulsory notification of diseases, injuries and public health events is essential for the monitoring of cases and the effectiveness of health surveillance actions, especially among vulnerable populations. Objective: Check how the scientific literature has addressed the outcome of treatment among indigenous children notified with diseases, injuries and public health events. Methodology: It is an integrative literature review based on the research question “How has the scientific literature addressed the treatment outcome among indigenous children notified with diseases, injuries and public health events?”, In the LILACS databases, PubMed (MEDLINE), EMBASE, SCOPUS and Web of Science. Free and controlled vocabulary was used with its synonyms in Portuguese, English and Spanish, combined by the Boolean operators AND and OR. Complete studies were included, in the aforementioned languages, and duplicate articles and reviews were excluded. Results: A total of 795 publications were found and, after applying the evaluated criteria, five papers were evaluated, which were carried out in Brazil, Australia, the United States of America and Canada, between 1976 and 2020, from malaria diseases, tuberculosis, pertussis, and bacterial meningitis, and notification related to external causes by fire. Children under one year of age had the highest death outcome, followed by children under five years of age. Conclusions: There are few studies related to the subject, whose predominance was bacterial diseases.